Os desafios e potencialidades da produção orgânica: análise do Projeto Cultivando Água Boa (CAB), na Bacia do Paraná 3 - Castro Neto, Nelson de (2011)
Family farming in organic agriculture sees a strategy to promote their economic and social development, adding value to their products. This new perspective has been constructed and expressed in the idea of "sustainability in the field." In this sense, the family farm and agro-ecological production, combined with the practices conscious consumption, can occupy an important place in the business landscape and represent an integrated environmental conservation, social and economic. Seeking to assist the manufacturer in the conversion of production, the Itaipu binational (IB) in 2003, through the project Cultivating Good Water (CAB), intended to encourage and assist farmers in 29 municipalities in Paraná Watershed 3 (BP3), located in West of Paraná. The question that guides this study is: from the perception of farmers, the conversion from conventional to organic production - from the CAB project - has brought benefits and value to producers involved in the project? The methodology used in this study was qualitative, with semi-structured interviews and descriptive analysis, assuming the character of a case study. The survey's target sectors were small farmers, associations, cooperatives and business management, linked to the CAB project. The results obtained in this work allowed a social and economic analysis with respect to the conversion of organic family farmers from the BP3. In the social aspect, it was possible to clarify questions about earnings, relationships and stimulate the creation of cooperation networks. In the economic aspect, it was found that for farmers converting to organic production means higher income and better economic expectations. For respondents, this type of cultivation is well suited to family farms, providing a cost reduction and less dependence on external inputs. In conclusion, we found that the main benefits brought to farmers in the region under study, refer to the issues surrounding community health, healthy eating and quality of life for everyone involved in organic production chain. However, advances are needed with regard to technical assistance and technology to increase production capacity.